Utilizing Passive Radiative Properties of Silver Ants - Markus Zimmerl; Paul Kaltenböck; Ille C. Gebeshuber (Proceedings)
The increasing occurrence of hot summer days causes stress for both humans and animals, particularly in urban areas where temperatures remain high, even at night [...]